2021
DOI: 10.1186/s40634-021-00396-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative pivot-shift accelerometry combined with anesthesia improves the measure of rotatory knee instability in anterior cruciate ligament injury

Abstract: Purpose The knee stiffness acquired following an Anterior Cruciate Ligament (ACL) injury might affect clinical knee tests, i.e., the pivot-shift maneuver. In contrast, the motor effects of spinal anesthesia could favor the identification of rotatory knee deficiencies prior to ACL reconstruction. Hence, we hypothesized that the intra-operative pivot-shift maneuver under spinal anesthesia generates more acceleration in the lateral tibial plateau of patients with an injured ACL than without. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
(63 reference statements)
1
13
0
Order By: Relevance
“…ɣ: Statistical significance for the non-preferred limb comparing before and after the match (p < 0.05). biomechanical behavior found for deficient ACL knees (Lam et al, 2011) and rotatory instabilities identified by the pivot shift maneuver (Caracciolo et al, 2021). In contrast, the lack of rotatory knee stability is an important risk factor for noncontact ACL rupture (Quatman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…ɣ: Statistical significance for the non-preferred limb comparing before and after the match (p < 0.05). biomechanical behavior found for deficient ACL knees (Lam et al, 2011) and rotatory instabilities identified by the pivot shift maneuver (Caracciolo et al, 2021). In contrast, the lack of rotatory knee stability is an important risk factor for noncontact ACL rupture (Quatman et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The test was repeated three times, obtaining the mean of both the preferred and non-preferred limbs to kick a ball. The delta between the maximum and minimum from the modulus of the acceleration during the reduction phase of the pivot shift maneuver was used (Caracciolo et al, 2021). The modulus of the acceleration has been estimated from the Euclidean norm 2 as a 2 a 2 x + a 2 y + a 2 z 2 in m*s −2 .…”
Section: Instrumented Pivot Shift Maneuvermentioning
confidence: 99%
See 3 more Smart Citations